Design method of radiant cooling area based on the relationship between human thermal comfort and thermal balance. (December 2017) - Gao, Song; Li, Yang; Zhao, Min; Wang, Yuang; Yang, Xiaohu; Yang, Chun; Jin, Liwen
Abstract: The radiant cooling air conditioning system has been widely applied, due to its features of better thermal comfort and efficient energy-saving. Most of the research on radiant cooling air conditioning system tends to concentrate on its cooling performance and energy-saving potential. However, the design methods of radiant cooling air conditioning system to guide its engineering application are rare. On the basis of the simplified human thermal balance equation and the linear relationship between the sensible heat loss and human thermal comfort achieved in our previous studies, the cooling performance of cooled surface is analyzed and then the method for determining the area of cooled surface is proposed in this paper. The numerical model is validated by experimental data and the calculation methods of cooled area are investigated with different boundary conditions. In addition, the PMV values in different heights and around human body are analyzed in detail. The results show that the calculation methods on account of the features of cooled surface could accurately predict the cooled area to maintain human thermal comfort under different conditions. Therefore, it is possible to determine the area of cooled surface in view of the relationship between human thermal comfort and thermal balance. This study could provide the guidelines for both the assessment of human thermal comfort and the system design of radiant cooling air conditioning system.